THE IMPACT OF KOREAN CELEBRITY ENDORSER AND ONLINE CUSTOMER REVIEW ON SOMETHINC CUSTOMER PURCHASE INTENTION MEDIATED BY BRAND IMAGE - Dellarosa, Ivana; Widyarini, Lydia Ari; Gunawan, Erick Theofilus (Universitas Nahdlatul Ulama Surabaya, 2025)
K-pop gains recognition and popularity because to the hallyu phenomenon, particularly in Indonesia. This phenomenon presents a chance for brands, particularly those in the beauty industry, to collaborate with K-pop and K-drama artists who align with their brand image in order to generate public interest in their product. Also, digitalization era situs gacor777 has caused people to search product review on social media platform as people spend more time on social media. People used to consult about particular products before making a new purchase to find out if they were good or not. In this study, 159 Somethinc users who have also made purchases are included. Google Forms have been used to distribute the questionnaires for participants to complete in order to contribute to this research. The information was gathered and examined using the Structural Equation Method (SEM), with the assistance of SMARTPLS 3.0's partial least square tool. The result of this research turns out that celebrity endorses and online customer review have positive and significant impact on brand image, the hypothesis is accepted. Celebrity endorser and brand image have positive and significant impact on purchase intention, the hypothesis is accepted. Online customer review has positive but no significant effect on purchase intention, therefore the hypothesis is rejected. Brand image is positive and significantly mediates the impact of celebrity endorser and online customer review on purchase intention.